Assessing Local Economic Empowerment Governance through the Palangka Raya Economic Heroes Program - Adithiya Wiradinatha Saputra; Febriomico Griando Rasan; Restu Marethya Pandra; Wayan Sulatri; Lola Kristina; Oktariangni Zega (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
Poverty remains a multidimensional issue affecting community welfare, particularly in access to economic opportunities, education, and social services. To address this issue, the Government of Palangka Raya implemented the Pahlawan Ekonomi Palangka Raya (PEP) Program as a community economic empowerment initiative aimed at reducing poverty through business assistance, entrepreneurship training, and mentoring. This study aims to analyze the governance of the PEP Program in poverty alleviation efforts in Palangka Raya. The research employed a qualitative method with a descriptive analytical approach. The subjects involved were representatives of the Social Service Office of Palangka Raya who directly participated in program management and implementation. Data were collected through interviews and documentation using interview guidelines and official supporting documents as research instruments. The data analysis process included data reduction, data presentation, and conclusion drawing. The findings indicate that the PEP Program contributed to improving community economic empowerment and supporting poverty alleviation through productive business development. However, challenges remain, including inaccurate beneficiary data, uneven program distribution, and weak monitoring systems. The study concludes that effective governance, transparency, and continuous evaluation are essential to improving program sustainability and effectiveness. The research also implies the importance of strengthening local government capacity and collaboration among stakeholders in implementing sustainable community empowerment policies effectively consistently.